An empirical study of Internet of Things (IoT) - based healthcare acceptance in Pakistan:pilot study - Solangi, Zulfiqar Ali; Solangi, Yasir Ali; S. Abd. Aziz, Madihah; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2018)
The motivation behind the study is to incorporate Health Belief Model (HBM) and Unified Theory of Acceptance and Use of Technology (UTAUT) model alongside trust and doctor-patient relationship keeping the ultimate objective to investigate the affirmation of IoT-based health services framework. In order to understand technological, and clinical context the proposed framework of this study is a synthesis of UTAUT, and HBM theories respectively, finally trust and doctor-patient relation factors are used to measure individual and patients' perspective about IoT-based health care systems. The proposed framework is validated with a pilot study of 40 respondents from five thickly populated cities of Pakistan. The findings verified that the proposed framework is appropriate to implement with empirical data. Based on the confirmation of the most familiar both theories, in health framework, this study demonstrates Perceived Health Risk which is composed of two independent factors, Perceived Susceptibility (PSS) and Perceived Severity (PS) have a significantly positive effect on cues to action. While in a technological context, Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), and Facilitating Conditions (FC) have a jointly significant positive effect on cues to action to use behavior. Furthermore, both trust and doctor-patient relationship have also a positive effect on cues to action to use behavior. The instrument questionnaire adopted cluster sampling, and structural equation modeling (SEM) to validate and test the hypotheses. The findings may be used and generalized to other similar population as a theoretical basis to improve the health care services of developing countries like Pakistan.